Extremism, Its Causes, and Its Negative Consequences for Society - Ali , Thawra (Islamic Sciences Journal, 2023)
ABSTRACT Researching, scrutinizing and revealing the roots of extremism, terrorism and violence in historical and religious sources and references are among the thorny, complex and important issues today, because they have become a serious issue of great importance in life, of Muslims. Extremism and the accompanying violence and terrorism can be attributed to several internal and external factors. The internal factors related to the lives of Muslims can be attributed to the exaggeration in the interpretation of the texts contained in the Qur’an and the Sunnah, and the lack of understanding of the reality of sciences and their applications. This exaggerated and extremist approach of some Islamic sects has reappeared today in a new dress, perhaps with an external motive to seduce Muslims, divide them, weaken their status, and make them into different sects conflicting among themselves. What helped the emergence of extremism, terrorism and the politics of violence is the wrong call that some sects are promoting today to return Islam to the religion (the predecessor) without to the truth of moderate Islam, the middle nation, Thus, the media difference became mouthpieces calling for the blasphemy of the violators, and even murder, and contributed to the media of the modern era of satellite channels, means of communication and publications, and it became easy for some ignorant people to see them, which contributed to the emergence of ISIS (external) extremism again.